2002
DOI: 10.1080/08941920290107675
|View full text |Cite
|
Sign up to set email alerts
|

Linking Local Perceptions of Elephants and Conservation: Samburu Pastoralists in Northern Kenya

Abstract: Abstract:This paper examines the development and implementation of a grassroots elephant conservation program based upon the Samburu people's perceptions and knowledge of elephants in the areas surrounding the Samburu and Buffalo Springs National Reserves in Northern Kenya. Ethnographic methods were used to understand these perceptions and demonstrated that strong customs and traditions for conserving wildlife, particularly elephants, exist among the Samburu people. It became evident that these customs are cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 14 publications
1
46
0
1
Order By: Relevance
“…For example, in a study of Tsonga communities in a more densely populated region adjacent to KNP to the south, Hunter et al (2010) found that environmental concern was strongly related to material needs and livelihoods, and this was gendered and varied substantially by village. This transition may be the result of increasing exposure to Christianity, alternative views of nature in educational institutions (Millar, 2004), economic development opportunities or cultural taboos (Kuriyan, 2002), and/or restrictions on resource use imposed by government and TAs, although such causal relationships were beyond the scope of our research.…”
Section: Community Needsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, in a study of Tsonga communities in a more densely populated region adjacent to KNP to the south, Hunter et al (2010) found that environmental concern was strongly related to material needs and livelihoods, and this was gendered and varied substantially by village. This transition may be the result of increasing exposure to Christianity, alternative views of nature in educational institutions (Millar, 2004), economic development opportunities or cultural taboos (Kuriyan, 2002), and/or restrictions on resource use imposed by government and TAs, although such causal relationships were beyond the scope of our research.…”
Section: Community Needsmentioning
confidence: 96%
“…For institutions responsible for conservation, detailed knowledge of the people whose lives are affected by conservation policies can be as important as information about the biodiversity to be conserved (Anthony & Bellinger, 2007;Brechin et al, 2002;Veech, 2003). Moreover, it has been noted that in addition to playing a key role in human-environment interactions (Nietschmann, 1992;Smith, 2001), cultural elements of nature protection can be a resource providing insight into development of conservation plans (Kuriyan, 2002;Stevens, 1997) while also reinforcing community identity and, promoting community cohesion and adaptability (Goodland, 1991;Kleymeyer, 1992;Robinson & Redford, 1994). Thus, recognition and understanding of different local cultural systems permits a broader, more appropriate overall policy toward natural resource use (Maffi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have maintained that variations in traditional cultural values are most important in shaping local peoples' perceptions of elephants. For example, Kuriyan (2002) conducted ethnographic studies among the Samburu pastoralists of Kenya and found that traditional beliefs about the importance of elephants were behind the community's support for elephant conservation, rather than monetary incentives.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of those affected by wild animals were critical of ACAP policy for not providing any compensation for heir losses. Many studies in and around similar protected areas have also found a positive correlation between problems with wild animals and unfavorable attitude toward protected areas and their policies (Mahanty and Russell 2002, Kuriyan 2002, Heinen 1998, Fiallo and Jacobson 1995, Nepal and Weber 1995.…”
Section: Discussionmentioning
confidence: 95%
“…Because of their political awareness, education, and experience of decades of conflict with the park authority, they possibly see the park as a local extension of the state authority repressing their social, cultural and economic freedoms (Lane and Chase 1996). As other findings suggest, residents of local communities in and around protected areas usually harbor unfavorable attitudes toward conservation authorities and their polices (Dearden 2002, Mahanty and Russell 2002, Kuriyan 2002, Maikhuri et al 2000, Heinen 1998, Fiallo and Jacobson 1995, Nepal and Weber 1995.…”
Section: Links Between Perception Attitudes and Participationmentioning
confidence: 96%